A prospective, randomised, placebo-controlled study to identify biomarkers associated with active treatment in psoriatic arthritis: effects of adalimumab treatment on synovial tissue. Issue 8 (22nd July 2008) - van Kuijk, A W R; Gerlag, D M; Vos, K; Wolbink, G; de Groot, M; de Rie, M A; Zwinderman, A H; Dijkmans, B A C; Tak, P P
Abstract : Objective: To determine which of the changes in synovial tissue correlates best with clinical response associated with effective therapy (adalimumab) to facilitate the planning of future studies with therapeutic agents for psoriatic arthritis (PsA). Methods: A total of 24 patients with active PsA were randomised to receive adalimumab (n = 12) or placebo (n = 12) for 4 weeks. Synovial biopsies were obtained before and after 4 weeks of treatment. Immunohistochemical analysis was performed to characterise the cell infiltrate, expression of cytokines and matrix metalloproteinases (MMPs) and vascularity. Sections were analysed by digital image analysis. Statistical analysis was performed using covariance analysis. Results: The mean Disease Activity Score in 28 joints (DAS28) after 4 weeks was 1.92 units lower (95% confidence interval (CI) 1.07 to 2.77) after adalimumab therapy compared with placebo. Paired pretreatment and post-treatment synovial samples were available from 19 patients. Many cell types were reduced after adalimumab treatment compared to placebo. After applying a ranked analysis of covariance (ANCOVA) model to correct for baseline imbalances, a significant effect of treatment was observed on CD3-positive cells: there was a median reduction of 248 cells/mm 2 after adalimumab versus placebo treatment (p = 0.035). In addition, the expression of MMP13 was significantly reduced after active treatment: the integrated optical density (IOD)/mm 2 was 18 190 lower after adalimumab treatment as compared to placebo (p = 0.033). Conclusion: Adalimumab therapy in PsA is associated with a marked reduction in T cell infiltration and MMP13 expression in synovial tissue, suggesting that these parameters could be used as biomarkers that are sensitive to change after active treatment in small proof of concept studies in PsA.